Fatawa on Shi'ism in Indonesia (1920-2012) : a critical analysis - Firdaus, Robitul
The presence of Shi'ism and Shi'is as a minority Muslim group in Indonesia has led to complex responses from the overwhelming Sunni majority. The Sunni responses range from being sympathetic to distasteful. This study examines the fatawa on Shi'ism as a response of Sunni 'ulama' to the growth and development of the Shi'is in Indonesia. Given by an Islamic expert ('ulama') or a jurisconsult (muftī), usually, but not necessarily, in answer to a question, a fatwa is an important instrument for 'ulamā' to express their authority and influence the religious attitude of Muslims. Specifically, the study focuses on six fatawa issued either by an individual or institutional Indonesian muftīs, namely the fatwa of Hasyim Asy'ari (1875-1947), the fatwa of MUI on Shi'ism (1984), the fatwa of MUI on temporary marriage (mut'ah) (1997), the fatwa of MUI's Structure of Sampang District (2012), the fatwa of the MUI's Structure of East Java Province (2012), and the fatwa of the Forum Ulama Ummat Indonesia (2012). These fatawa are scrutinised from the methodological and socio-political points of view. This descriptive-qualitative research employs content and discourse analysis and obtains data from both secondary and primary sources. The findings of this study reveal that the six fatawa are not methodologically formulated in a single pattern and their contents cover theological and ritual aspects of Shi'ism. It is also found that the fatawa vary in terms of their social and political surroundings. Unlike the fatwa of Hasyim Asy'ari, two fatawa on Shi'ism during the New Order regime were influenced by political interests, while other fatawa in the Reform era witnessed the political power of fatwa in the construction of government policy. Nevertheless, although they might be issued in a response to socio-political circumstances, their main goals were clearly theological. Furthermore, the study argues that a strong connection between fatwā and violence is not proven. It is suggested that the violence was not solely contributed by the fatwa. Complex social and political factors also played a role in the rise of violence toward Shi'is and Shi'i institutions. After all, since a fatwa is naturally not binding for Muslims in Indonesia, the Sunni 'ulama' should also enhance the understanding of Sunnis with regard to their own religious thought and tradition, instead of relying only on the fatwa to prevent the spread of Shi'ism.